Próba ukierunkowania rehabilitacji u pacjentów ze stwardnieniem rozsianym w zależności od typu klinicznego choroby = The attempt conditions for the rehabilitation of patients with multiple sclerosis, depending on the type of clinical disease - Garczyński, Wojciech; Krajewski, Stanisław (Journal of Education, Health and Sport, 2016)
Garczyński Wojciech, Krajewski Stanisław. Próba ukierunkowania rehabilitacji u pacjentów ze stwardnieniem rozsianym w zależności od typu klinicznego choroby = The attempt conditions for the rehabilitation of patients with multiple sclerosis, depending on the type of clinical disease. Journal of Education, Health and Sport. 2016;6(7):35-58. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.56870 http://ojs.ukw.edu.pl/index.php/johs/article/view/3655 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 25.05.2016. Revised 25.06.2016. Accepted: 28.06.2016. Próba ukierunkowania rehabilitacji u pacjentów ze stwardnieniem rozsianym w zależności od typu klinicznego choroby The attempt conditions for the rehabilitation of patients with multiple sclerosis, depending on the type of clinical disease Wojciech Garczyński 1,2, Stanisław Krajewski 3,4 1 Wyższa Szkoła Edukacji i Terapii w Poznaniu, Wydział Studiów Edukacyjnych, ul. Grabowa 22, 61-473 Poznań 2 Indywidualna Praktyka Fizjoterapeutyczna, ul. Biskupa Bandurskiego 71/17, 71-685 Szczecin 3 Bydgoska Szkoła Wyższa ul. Unii Lubelskiej 4; 85-059 Bydgoszcz 4 Klinika Neurochirurgii 10 Wojskowy Szpital Kliniczny z Polikliniką, ul. Powstańców Warszawy 5, 85-681 Bydgoszcz Autor korespondencyjny: dr n. o zdr. Wojciech Garczyński Indywidualna Praktyka Fizjoterapeutyczna ul. Biskupa Bandurskiego 71/17 71-685 Szczecin w.garczynski@gmail.com Słowa kluczowe: rehabilitacja, stwardnienie rozsiane. Key words: rehabilitation, multiple sclerosis. WSTĘP. Stwardnienie rozsiane (łac. sclerosis multiplex, SM) jest to choroba o podłożu zapalno-demielinizacyjnym ośrodkowego układu nerwowego, w której dochodzi do wieloogniskowych zmian. Etiopatogeneza związana jest z uwarunkowaniami genetycznymi i immunologicznymi. Stwardnienie rozsiane może mieć przebieg z rzutami lub bez. Forma kliniczna pierwotnie postępująca (PPMS) stwardnienia rozsianego występuje bez rzutów, pozostałe formy kliniczne: rzutowo – remisyjna (RRMS), wtórnie postępująca (SPMS) i postępująco – nawracająca (PRMS) charakteryzują się pojawianiem się rzutów choroby, forma łagodna (BNMS) może występować bez rzutów. CEL BADAŃ. Głównym celem podjętych badań było poszukiwanie zależności pomiędzy zróżnicowaniem funkcji fizycznych chorych na stwardnienie rozsiane a typem klinicznym schorzenia. Ewentualne znalezienie takich zależności w konsekwencji pozwoliłoby na wczesne ukierunkowanie procesu rehabilitacji dostosowanej do potrzeb pacjentów z określonym typem klinicznym choroby. MATERIAŁ I METODA. W badaniu wzięło udział 313 osób ze zdiagnozowanym stwardnieniem rozsianym, przebywających na czterotygodniowych turnusach rehabilitacyjnych w Centrum Rehabilitacji dla Osób Chorych na Stwardnienie Rozsiane im. Jana Pawła II w Bornym Sulinowie. Zastosowano metodę sondażu diagnostycznego z wykorzystaniem standaryzowanych kwestionariuszy, typowych do oceny funkcji u chorych na stwardnienie rozsiane (EDSS, MFIS, MDST, HADS, EQUI – SCAL). Do obliczeń statystycznych wykorzystano program Statistica 10 firmy StatSoft. WYNIKI. Uzyskano statystycznie istotne różnice w wieku zachorowania na stwardnienie rozsiane oraz w średnim czasie trwania choroby z podziałem na formy kliniczne (odpowiednio p<0,001 i p<0,01). Na podstawie testu Kruskala - Wallisa stwierdzono istotne statystycznie różnice w poziomie niewydolności ruchowej - EDSS (p<0,001), zmęczenia – MFIS (p<0,05), równowagi – EQUI SCALE (p<0,001) i niesprawności – MDST (p<0,01) w typach klinicznych stwardnienia rozsianego. WNIOSKI. 1. Poziom zmęczenia, zakres zaburzeń równowagi, poziom niewydolności ruchowej oraz niesprawności zależą od typu klinicznego SM. 2. Poziom objawów lękowych i depresyjnych nie wykazuje zróżnicowania pod względem typu klinicznego SM. 3. Pomimo występowania pewnego zróżnicowania poziomu wybranych funkcji fizycznych i społecznych zależnie od typu SM, trudnym wydaje się ukierunkowanie rehabilitacji w oparciu o te założenia. INTRODUCTION. Multiple sclerosis (eng. Multiple sclerosis, MS) is an inflammatory-demyelinating disease of the central nervous system, wherein the multifocal changes occur. Etiopathogenesis is related to genetics and immune. Lesions are characterized by rapid progression and are mainly found in the white matter, brainstem, cerebellum, spinal cord and optic nerve. In remission, remyelination occurs, following which the inflammation subsides. Multiple sclerosis can run with or without relapses. Clinical form of primary progressive (PPMS), multiple sclerosis occurring without relapses, other clinical forms: relapsing - remitting (RRMS), secondary progressive (SPMS) and progressive - relapsing (PRMS) are characterized by the appearance of relapses, a form of benign (BNMS) may be present without relapses. OBJECTIVES. The main objective of this study was to examine correlations between the diversity of physical and social functions in patients with multiple sclerosis and the type and form of the disease. Possible to find such relations, in consequence, would enable an early orientation of rehabilitation process for needs of patients with a particular type and form of the disease. MATERIAL AND METHODS. The study involved 313 patients (215 women and 98 men) diagnosed with multiple sclerosis staying on the four-week rehabilitation courses at the Pope John Paul II Center of Rehabilitation for People with Multiple Sclerosis in Borne Sulinowo. The method of diagnostic survey, based on a survey technique using standardized scales and questionnaires to assess the typical functions in patients with multiple sclerosis (EDSS, MFIS, MDST, HADS, EQUI - SCAL). For the statistical calculation StatSoft Statistica 10 was used. RESULTS. On the basis of the Kruskal – Wallis test statistically significant differences in the level of physical failure were found - EDSS (p <0.001), fatigue - MFIS (p <0.05), balance - EQUI SCALE (p <0.001) and disability - MDST (p <0.01) in clinical forms of multiple sclerosis. CONCLUSIONS. 1. The level of fatigue, imbalances, motor failure experienced by the patient depends on the clinical form of MS and shows no variation with respect to the type of disease. 2. Level of anxiety and depression symptoms does not have diversity in terms of form of multiple sclerosis. 3. Despite the prevalence of certain differentiation in some of the physical and social functions depending on the form and type of multiple sclerosis, it seems difficult to orientate rehabilitation based on these assumptions. It seems more important to individualize the process based on the nature and pace of the disease and taking into account the current patient’s symptoms.